The complete genome sequences of Bacillus velezensis B26: a promising biocontrol agent and biofertilizer [version 2; peer review: 1 approved, 2 approved with reservations] - Sandeep Mallya; Kiran Kumar Kolathur; Subrahmanyam Volety Mallikarjuna; Venkatesh Kamath B (F1000Research)
Bacillus velezensis, is a bacterium widely recognized for its biocontrol properties and ability to promote plant growth. This study presents the whole genome sequence of B. velezensis B26, a newly identified strain isolated from chicken carcass soil, Udupi, India. The bacterium showed strong activity against fungal pathogens and exhibited diverse enzymatic activities. The whole genome sequencing was executed using Illumina technologies. Assembly revealed that strain B26 possesses a genome of 3,946,698-bp with a G+C content of 46.3%. Genome annotation identified 3776 protein-coding genes, 1 rRNA gene, 50 tRNA genes, 5 ncRNA genes, and 59 pseudogenes. Functional analysis of the B. velezensis B26 genome revealed 216 genes involved in carbohydrate metabolism, 3 genes in potassium metabolism, 148 genes linked for cofactors, vitamins, prosthetic groups and pigments, 10 genes involved in phosphorus metabolism, 24 genes associated with iron acquisition and metabolism, 20 genes for nitrogen metabolism, 6 genes involved in sulfur metabolism, 6 genes in secondary metabolism, 12 genes associated with metabolism of aromatic compounds, 43 genes involved in stress response and 36 genes associated with virulence, disease and defense. The raw sequence data generated in this work has been deposited in the NCBI database and the genome sequence is available under the accession number JAYKOV000000000. This genomic data provides insight into the biocontrol ability and plant-growth promoting capabilities of B. velezensis B26.